SCHWARZSCHILD-DE SITTER AND MECHANICAL APPROACHES COMPARISON WITH RESPECT TO DARK MATTER HALOS - Brilenkov, R.; Eingorn, M.; Zhuk, A. (Одеські астрономічні публікації, 2013)
We compare the Schwarzschild-de Sitter approach to deriving mass and potential distributions and corresponding parameters associated with dark matter halos for clusters of galaxies with the mechanical one, taking into account cosmological effects, in particular, dark energy influence.